THE INFLUENCE OF MILENIAL GENERATION CREATIVITY AND SOCIAL MEDIA USE ON THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) AT DKI JAKARTA - Harits Rifqi Muhanda; Nurjanah, Siti; Sudiarditha, I Ketut R. (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The Covid-19 epidemic, as we are all aware, is causing havoc around the globe and is delaying the economy's growth. Therefore, a pandemic may be viewed as a flow of change that takes place, and business owners need to be able to manage this flow of change in order for their company to survive. This study aims to identify and analyze the influence of the creativity of millennial generation MSMEs and the use of social media on business development in MSMEs in the DKI Jakarta area. This study is a quantitative investigation that gathers information in the form of numerical data, which is then processed and analyzed to learn more about the meaning of the data. More specifically, this study used a survey method along with a regression strategy. The study will be conducted in Jakarta, Indonesia's Special Capital Region. All creative economy participants in DKI Jakarta, including up to 115 MSME participants, including small and medium- sized enterprises, were included as the study's sample. The use of social media and creativity are positively correlated. Utilizing social media more and being more creative will all aid in the growth of MSMEs. Micro, small, and medium-sized enterprises (MSMEs) will diminish as innovation and social media use decline